Notions of healing and transcendence in the trajectory of African traditional religion: paradigm and strategies - Essien, Essien D. (International Review of Mission, 2013)
This paper examines the import of transcendence in illnesses and misfortunes as well as the place of healing in African traditional religion. The belief in medicine among Africans is the art of using available forces of nature to prevent disease and to restore and preserve health. It occupies a prominent position in the religious lives of African people. This article draws attention to the practice of several healing activities in African traditional religion in its attempts to restore health, exploring the indigenization of health care procedures and the role and function of God in African medicine and healing. This work shows that the concept of God is central in African religion and plays a prominent role in its healing ministry. The paper concludes with a suggestion about what could constitute a collective synergy for Western orthodox and African traditional medicine.
free
Keywords: Christianity and African religions; God – Comparative studies; Gods and goddesses; African; Leadership; Religious – African religions; Medicine and religion; Shamans; Traditional medicine; Transcendence